Perbandingan Pengakuan Pendapatan dalam Akuntansi Syariah dan Konvensional: Kajian Literatur - Iffatun Nafsiyah; Sami Ayu Lestari (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Revenue recognition represents a fundamental aspect of financial reporting, influencing the reliability and comparability of financial information across different accounting systems. This study compares revenue recognition practices in Islamic and conventional accounting by examining their underlying principles, applicable accounting standards, and practical implications. A qualitative library research approach was employed through the analysis of textbooks, scholarly articles, accounting standards, and relevant regulations. Data were analyzed using a descriptive-comparative method to identify similarities and differences between the two accounting frameworks. The findings indicate that conventional accounting recognizes revenue based on the accrual basis and the principle of economic realization, whereby revenue is recorded once the right to receive economic benefits has arisen, regardless of cash receipt. In contrast, Islamic accounting applies the accrual basis within the framework of Sharia principles and relevant PSAK Sharia standards, emphasizing compliance with the prohibition of riba, gharar, and maisir. Consequently, revenue recognition in Islamic contracts, including murabahah, salam, istisna', and ijarah, reflects both economic substance and ethical considerations. Although both systems share similar conceptual foundations, Islamic accounting places greater emphasis on transparency, justice, and Sharia compliance in financial reporting.